Enhancing Academic Outcomes in Madrasah Tsanawiyah: Examining the Effects of Classroom Discipline and A Supportive Work Environment - Offirstson, Topic; Salam DZ, Abdus; Karim, Abdul; Azzam, Hamadah; Muhamad, Nur (JURNAL AL-TANZIM, 2025)
This study aims to examine the influence of classroom discipline and work environment on the performance of Madrasah Tsanawiyah teachers, while developing the conceptual Discipline–Environment Symbiosis Model (DESM) within the context of Islamic education. Employing a convergent mixed-methods design, quantitative data were collected from 210 teachers using standardized questionnaires and analyzed through Partial Least Squares Structural Equation Modeling (PLS-SEM). Qualitative data were obtained via in-depth interviews and thematically analyzed. Quantitative findings indicate that both classroom discipline and the work environment have a significant positive effect on teacher performance (p < 0.05), with classroom discipline having the most significant impact. Qualitative insights reveal that procedural consistency, collegial support, and alignment with Islamic values are key factors in enhancing performance. The integration of both data strands resulted in the DESM, which emphasizes the synergy between effective classroom management and a supportive work environment as prerequisites for successful teaching and learning. This model offers theoretical contributions to value-based educational management and practical implications for policymakers and school leaders in designing interventions to improve teacher performance. Future research is recommended to test the DESM across different educational levels and cultural contexts to broaden its external validity.